Effects of Delayed Visual Feedback on Grooved Pegboard Test Performance - Fujisaki, Waka (Frontiers in Psychology, 2012)
Using four experiments, this study investigates what amount of delay brings about maximal impairment under delayed visual feedback and whether a critical interval, such as that in audition, also exists in vision. The first experiment measured the Grooved Pegboard test performance as a function of visual feedback delays from 120 to 2120 ms in 16 steps. Performance sharply decreased until about 490 ms, then more gradually until 2120 ms, suggesting that two mechanisms were operating under delayed visual feedback. Since delayed visual feedback differs from delayed auditory feedback in that the former induces not only temporal but also spatial displacements between motor and sensory feedback, this difference could also exist in the mechanism responsible for spatial displacement. The second experiment was hence conducted to provide simultaneous haptic feedback together with delayed visual feedback to inform correct spatial position. The disruption was significantly ameliorated when information about spatial position was provided from a haptic source. The sharp decrease in performance of up to approximately 300 ms was followed by an almost flat performance. This is similar to the critical interval found in audition. Accordingly, the mechanism that caused the sharp decrease in performance in experiments 1 and 2 was probably mainly responsible for temporal disparity and is common across different modality–motor combinations, while the other mechanism that caused a rather gradual decrease in performance in experiment 1 was mainly responsible for spatial displacement. In experiments 3 and 4, the reliability of spatial information from the haptic source was reduced by wearing a glove or using a tool. When the reliability of spatial information was reduced, the data lay between those of experiments 1 and 2, and that a gradual decrease in performance partially reappeared. These results further support the notion that two mechanisms operate under delayed visual feedback.